Adoption, use and management of process mining in practice. Issue 2 (1st December 2020) - Grisold, Thomas; Mendling, Jan; Otto, Markus; vom Brocke, Jan
Abstract : Purpose: This study explores how process managers perceive the adoption, use and management of process mining in practice. While research in process mining predominantly focuses on the technical aspects, our work highlights organizational and managerial implications. Design/methodology/approach: We report on a focus group study conducted with process managers from various industries in Central Europe. This setting allowed us to gain diverse and in-depth insights about the needs and expectations of practitioners in relation to the adoption, use and management of process mining. Findings: We find that process managers face four central challenges. These challenges are largely related to four stages; (1) planning and business case calculation, (2) process selection, (3) implementation, and (4) process mining use. Research limitations/implications: We point to research opportunities in relation to the adoption, use and management of process mining. We suggest that future research should apply interdisciplinary study designs to better understand the managerial and organizational implications of process mining. Practical implications: The reported challenges have various practical implications at the organizational and managerial level. We explore how existing BPM frameworks can be extended to meet these challenges. Originality/value: This study is among the first attempts to explore process mining from the perspective of process managers. It clarifies important challenges and points to avenues for future research.